Good News - Bad News: The Two Faces of Immune Privilege - Joan Stein-Streilein (Frontiers Research Topics, 2014)
Immune privilege was once thought to be the property of a few select sites that include the eye, brain, testis, pregnant uterus and (of all things) the hamster cheek pouch, and was believed to be mainly based on sequestration behind blood-tissue barriers. This view has changed. Immune privilege is now considered to constitute a more general phenomenon through which tissues are able to actively direct and control immune responses taking place in their "territory" to preserve their structural and functional integrity in the face of inflammatory processes. These positive aspects of immune privilege can be hijacked by tumors to their survival advantage and to the detriment of the host. This Research Topic dissects the beneficial and deleterious consequences of immune privilege in terms of the cellular and molecular mechanisms that various tissues and tumors use, each in its own fashion, to regulate immune processes that affect them, at the local and the systemic level.